2016
DOI: 10.2528/pierl16051305
|View full text |Cite
|
Sign up to set email alerts
|

A CPW-Fed Dual-Band Slot Antenna With Circular Polarization

Abstract: Abstract-In this paper, a coplanar waveguide (CPW)-fed dual-band slot antenna with circular polarization (CP) is presented. In order to achieve CP characteristic, an asymmetric slot and F-shaped end patch are introduced to a conventional rectangular slot antenna. Moreover, by cutting a T-shaped notch on the ground plane, the axial ratio (AR) bandwidth (ARBW) can be extended. The antenna shows left-hand CP (LHCP) radiation in the boresight direction (i.e., +Z direction) at both ARBWs. The proposed antenna is fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Table 6 shows the comparison of proposed antenna with reported literature on broadband CP antennas. Reported antennas in [4][5][6][7], provide wideband/multiband CP response with small 3-dB ARBW and IBW and relatively large size. The antennas reported in [8][9][10][11][12][13][14][15][16][17][18] provide broadband CP with large physical dimensions, narrow 3-dB ARBW bandwidth, and small gain as compared to the proposed antenna.…”
Section: Radiation Pattern Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 6 shows the comparison of proposed antenna with reported literature on broadband CP antennas. Reported antennas in [4][5][6][7], provide wideband/multiband CP response with small 3-dB ARBW and IBW and relatively large size. The antennas reported in [8][9][10][11][12][13][14][15][16][17][18] provide broadband CP with large physical dimensions, narrow 3-dB ARBW bandwidth, and small gain as compared to the proposed antenna.…”
Section: Radiation Pattern Measurementmentioning
confidence: 99%
“…However, in recent years numerous CP techniques have been reported in the literature such as single/dual-feed, fractal structure, and loading of different shapes of strips/slots/stubs on radiating patch and/or ground plane to achieve CP by creating perturbation in electric field which excites two field components of equal magnitude and phase quadrature. Different techniques have been reported in the literature to produce wideband [3][4][5]/multiband [6,7]/broadband [8][9][10][11][12][13][14][15][16][17][18][19][20] circular polarization characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…A CPW-fed slot antenna is realized by embedding a vertical stub with the T-shaped strip and a slit to the ground plane as reported in [22] for realizing dual-band operations. Various dual-band antenna designs include symmetrically introducing four slot stubs on lateral arms [23], by an asymmetric slots in F-shaped end patch [24], by backed ground plane with radial stub on two identical elements [25], by using two parallel monopoles, one curved and one fork-shaped [26], by monopole structure with two inverted U-shaped, L-shaped lateral stubs [27], with two rectangular parasitic elements and an I-shape grounded stub [28], by printed log-periodic dipole array (LPDA) [29], by slots and monopole antenna [30], and by employing meander line technique in [31]. A theoretical and experimental study of twin-slot multilayer CPW-fed antenna is reported in [32], and highly selective behavior and regulation of sharp variations of a discontinuous parallel-plate waveguide with a narrow rectangular ridge filled with axially anisotropic material identified using mode matching technique is achieved in [33].…”
Section: Introductionmentioning
confidence: 99%